An accurate fingerprint reference point determination method based on curvature estimation of separated ridges - Doroz, Rafał; Wróbel, Krzysztof; Porwik, Piotr (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents an effective method for the detection of a fingerprint?s reference point by analyzing fingerprint ridges` curvatures. The proposed approach is a multi-stage system. The first step extracts the fingerprint ridges from an image and transforms them into chains of discrete points. In the second step, the obtained chains of points are processed by a dedicated algorithm to detect corners and other points of highest curvature on their planar surface.
Keywords: biometrics; image processing; fingerprint recognition; Kolmogorov-Smirnov statistical test; reference point